The impact of employees' relationships on tacit knowledge sharing. Issue 4 (2nd November 2015) - Zhang, Xiaohong; Long, Chengfeng; Wang, Yanbo; Tang, Gaowen
Abstract : Purpose: – This paper aims to study the impact of individual relationships on tacit knowledge sharing in the company setting of compulsory bond, expressive bond, instrumental bond and self-monitoring by empirical explorations. Design/methodology/approach: – The paper raises seven hypotheses that focus on the impact of employees' relationship with tacit knowledge sharing in knowledge-intensive industries and positions based on relationship theory. Before distributing the formal questionnaires, a pre-research was done in a college by collecting comments and suggestions so as to correct and modify the questionnaires. A four-page questionnaire based on the Likert scale with 45 questions was used for data collection, and 210 valid questionnaires were collected from a research institute, a software company and an educational institute. Finally, SPSS17.0 was used to analyze these data, including reliability analysis, validity analysis, correlation analysis and regression analysis, etc. Findings: – The findings include: there is a positive correlation between employees' compulsory bond and the efficiency of tacit knowledge sharing; there is a positive correlation between employees' expressive bond and the efficiency of tacit knowledge sharing; there is a negative correlation between employees' instrumental bond and the efficiency of tacit knowledge sharing; the more apt employees are at self-monitoring, the more effectively they will share tacit knowledge; the interaction between compulsory bonds and self-monitoring has a positive and stimulating impact on tacit knowledge sharing; the interaction between expressive bonds and self-monitoring has a positive and stimulating impact on tacit knowledge sharing; and the interaction between instrumental bonds and self-monitoring has a certain impact on tacit knowledge sharing. Research limitations/implications: – However, the efficiency of tacit knowledge sharing cannot be measured easily and how to share the tacit knowledge based on employees' relationships should be further concerned by knowledge industries. Practical implications: – This paper illustrates multiple, in-depth approaches to research on knowledge sharing. It shows why it is important to pay attention to employees' relationships during the process of tacit knowledge sharing. The author argued some key factors such as compulsory bond, emotional bond and self-monitoring that may have a certain impact on the tacit knowledge sharing. The paper also further discussed the influence on the sharing of tacit knowledge as for the interaction between different relationship types and self-monitoring. Social implications: – The knowledge is critical to enhance enterprises' performance, and it will become more useful when the new knowledge is shared with others. However, tacit knowledge cannot be measured easily, and how to share the tacit knowledge based on employees' relationships should be further concerned by knowledge industries. A series of findings are proposed in this paper. Originality/value: – Integrating the knowledge of different individuals, of which 90 per cent is tacit knowledge, in an organization that engages in producing products and providing service is instrumental to the sustainability and productivity of that organization. This study addressed the factors and dynamics of tacit knowledge sharing that can be used in knowledge management to effectively capture, store and disseminate tacit knowledge across an organization.